Spectroscopic studies of Nd3+ ternary amino acid complexes - Tandon, S.; Bishnoi, N.; Surana, S. (Rev. Téc. Fac. Ing. Univ. Zulia)
The absorption spectra of six Nd3+ ternary amino acid complexes have been recorded in water. Nine bands in the region 400-800 nm have been observed. Slater-Condon, Lande’ spin-orbit interaction and Judd-Ofelt intensity parameters from the observed bands have been computed. Using these parameters energies and intensities of these bands have been calculated. The agreement between the calculated and observed values is good. The variation of all the parameters in the complexes from the corresponding Nd3+ aquo ion parameters has been discussed. Using F2 values, the nephelauxetic ratio and bonding parameter have been computed which indicate covalent character in these complexes.